Sedimentary organic matter signature hints at the phytoplankton-driven biological carbon pump in the central Arabian Sea - M. Pandey; M. Pandey; H. Biswas; H. Biswas; D. Birgel; N. Burdanowitz; B. Gaye (Biogeosciences)
The central Arabian Sea, a unique tropical basin, is profoundly impacted by monsoon wind reversal affecting its surface circulation and biogeochemistry. Phytoplankton blooms associated with high biological productivity and particle flux occur in the northern part of the central Arabian Sea due to summer-monsoon-induced open-ocean upwelling and winter convection. The core oxygen minimum zone (OMZ) at intermediate water depths is another important feature of the northern central Arabian Sea and fades southward. In this study, we attempt to interlink how these factors collectively impact phytodetrital export to the sediment. Short sediment core-top (1 cm) samples representing the recent particle flux signatures were analysed from five locations (21 to 11° N; 64° E) in the central Arabian Sea. Previously, we used core-top (0–0.5 cm) samples and observed a trend between diatom frustule abundance and diversity with bulk sedimentary parameters indicating a spatial variability in phytodetrital export to the sediment. To verify this observation further, lipid biomarkers of key phytoplankton groups and a sea surface temperature (SST) proxy have been analysed in addition to diatom frustules. The C37 alkenone-based SST proxy indicated cooler SST (27.6 ± 0.25 °C) in the north (21–15° N) mostly due to upwelling (summer) and convective mixing (winter). Warmer SSTs (+0.4 °C) are measured in the south, which usually remains nutrient-poor. This trend was consistent with satellite-derived average SST values (2017–2020). Lipid biomarker analysis suggests that dinoflagellates were likely to be the highest contributor, as indicated by dinosterol and its degradative product dinostanol, followed by brassicasterol and C37 alkenone, likely representing diatoms and coccolithophores, respectively. The north, which largely experiences periodic phytoplankton blooms and is influenced by the thick OMZ, revealed the highest contents of organic matter, diatom frustules (diversity and abundance), dominated by large, thickly silicified cells (e.g. Coscinodiscus and Rhizosolenia) and phytoplankton lipid biomarkers, as well as lower contents of zooplankton biomarkers (cholesterol and cholestanol). In contrast, relatively smaller chain-forming centric (e.g. Thalassiosira) and pennate (e.g. Pseudo-nitzschia, Nitzschia, Thalassionema) diatom frustules along with lower phytoplankton lipid biomarker contents were found in the south, where zooplankton biomarkers and silicious radiolarians were more abundant. The possible impacts of the OMZ on particle flux related to the phytoplankton community, including zooplankton grazing and other factors, have been discussed.